ANALYZING THE POTENTIAL OF CARBON TAX IMPLEMENTATION IN INDONESIA: A COMPREHENSIVE EXAMINATION FOR MITIGATING AIR POLLUTION - Tomy Prasetia (Jurnal Akuntansi dan Pajak, 2024)
Abstract Air pollution poses a significant threat to public health and the environment, particularly in densely populated urban areas and industrial centers. This paper explores the potential of implementing a carbon tax as a strategy to address both income generation and air pollution control in Indonesia. Drawing upon successful experiences in countries like Sweden, Finland, and Denmark, the study analyzes the potential impact of a carbon tax on carbon dioxide emissions in Indonesia. The research aims to assess the urgency of implementing a carbon tax in Indonesia, given its high carbon emissions and severe air pollution challenges. Based on a comprehensive literature review and analysis, this study explores the potential of a carbon tax in Indonesia as a means to generate revenue and control air pollution, providing valuable insights into the urgency and feasibility of such a policy intervention. The findings suggest that a well-designed carbon tax can serve as an effective tool for Indonesia to simultaneously address its economic and environmental challenges. The paper concludes by highlighting the importance of political will, stakeholder engagement, and careful policy design in implementing a carbon tax in Indonesia. The study's recommendations can inform policymakers and stakeholders in formulating effective strategies to combat air pollution, reduce carbon emissions, and generate sustainable revenue streams. By adopting a carbon tax, Indonesia can take significant steps towards a cleaner, healthier, and more prosperous future.